Trophic classification of aquatic insects in eight sheltered streams of the Colombian coffee ecoregion. (Universitas Scientiarum, 2010)
Objective. To determine the trophic structure of an aquatic insect assembly associated to eight streams in the Colombian coffee-growing ecoregion. Materials and methods. Aquatic insects were collected in eight forested streams located in La Vieja river basin. The taxa collected were assigned to dietary groups according to a regional classification based on the gut content analysis of aquatic insects associated to forested streams of the Otún river basin. Results. 2019 individuals belonging to 73 taxa were collected and 60 were classified into dietary groups. The most abundant group was collectors (55%), followed by shredders (31%) and predators (10%). Scrapers represented only 0.05% of the sample and the remaining 3.95% could not be classified due to lack of information. Conclusions. The dominance of collectors and shredders reveals the importance of coarse particulate organic matter (leaf litter) as a food resource for the insect fauna. Similarities between the trophic structure of this community and other communities studied in similar streams, suggest the possibility of a common pattern for Andean streams. This study evidenced the absence of knowledge on trophic ecology of tropical aquatic insects; 50% of the taxa collected had no associated information for the tropics and 20% had no information neither for the tropics nor temperate zones. Key words: Andean streams, aquatic insects, dietary groups, trophic structure, tropical ecosystems.